HPV Vaccines: Current Status - Mustafa Erkan Sarı; Mehmet Mutlu Meydanlı (Medical Network, 2017)
Abstract Cervical cancer is the fourth most common cancer in women worldwide, and the main cause is Human Papillomavirus (HPV) infection. HPV vaccines have had dramatic impacts on the prevalence of targeted HPV types (6,11,16 and 18), genital warts and precancerous cervical lesions. The World Health Organization (WHO) and Centers for Disease Control and Prevention (CDC) have confirmed the safety of HPV vaccines after >250 million doses were administered worldwide. WHO approved the two-dose-schedule of HPV vaccines in females younger than 15 years of age, with ≥6 month intervals. Extension of vaccination to men could further reduce the population prevalence of HPV and provide direct protection of men against genital warts and anal, penile and oropharyngeal cancers. The nine-valent HPV vaccine has demonstrated equivalent protection against the four types in the quadrivalent vaccine and high efficacy against the next five commonest causes of cervical cancer (HPV types 31,33,45,52 and 58). The Advisory Committee on Immunization Practices (ACIP) recommends the nine-valent vaccine and it has been approved by the FDA in 2014 for both genders between 11-12 years of age.